Text- und Literargeschichtliche Überlegungen zum Levispruch im Mosesegen (Dtn 33,8-11) - Schulz, Sarah (Biblica, 2024)
Based on a thorough text- and literary-historical analysis, the article examines the multi-faceted profile of the Levitical priesthood that Deut 33,8-11 successively develops in the course of the text’s redactional reworking. By collaging various statements about the distinctive qualities and functions of Levi/the Levitical priests at the end of the Pentateuch, it emphasizes the prominent role of the priests for the Jewish community. The Levi passage thus proves to be an important precursor of para-biblical texts such as the Book of Jubilees and the Aramaic Levi Document, which show a growing interest in the priesthood of Levi.